2004
DOI: 10.1088/0031-9155/49/18/015
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear cardio-respiratory interactions revealed by time-phase bispectral analysis

Abstract: Abstract. Bispectral analysis based on high order statistics, introduced recently as a technique for revealing time-phase relationships among interacting noisy oscillators, has been used to study the nature of the coupling between cardiac and respiratory activity. Univariate blood flow signals recorded simultaneously by laser-Doppler flowmetry on both legs and arms were analysed. Coupling between cardiac and respiratory activity was also checked by use of bivariate data and computation of the cross-bispectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Next we need to deal with the couplings between the cardiac and respiration phases, . It is already established from the results of methods specifically developed for detecting the coupling directionality of interacting phases [26,27,[29][30][31], and with direct physiological observations, that respiration drives the heart more than the reverse. Moreover, these coupling terms should have perturbation characteristics comparable to natural frequencies ω 1,2 .…”
Section: A Model For the Resultsmentioning
confidence: 99%
“…Next we need to deal with the couplings between the cardiac and respiration phases, . It is already established from the results of methods specifically developed for detecting the coupling directionality of interacting phases [26,27,[29][30][31], and with direct physiological observations, that respiration drives the heart more than the reverse. Moreover, these coupling terms should have perturbation characteristics comparable to natural frequencies ω 1,2 .…”
Section: A Model For the Resultsmentioning
confidence: 99%
“…Specifically, the bi-spectral analysis examines the relationships between the oscillations at two basic frequencies, fr(respiration mode frequency), fh(heartbeat mode frequency) and 2fr, 2fh and a modulation component at the frequency fr ± fh and etc. [30] (a) Heart motion bi-spectrum mesh plot (b) Heart motion bi-spectrum contour plot Figure 3. Heart motion bi-spectrum plot Figure 3 presents a typical bi-spectrum for the whole frequency domain for heart motion signal.…”
Section: Nonlinear Dynamics and Bi-spectral Analysismentioning
confidence: 99%
“…The nature of the couplings has been extensively studied from measured data in recent years [4][5][6][7][8][9][10][11][12][13]. Recently, Schäfer et al [14,15] and Rosenblum et al [16] found that there were sufficiently long periods of hidden synchronization and concluded that the cardiorespiratory synchronization and respiratory sinus arrhythmia (RSA) are two competing factors in cardiorespiratory interactions.…”
Section: Introductionmentioning
confidence: 99%